Photoelectric interactive response flexible sensor and preparation method thereof
By combining the MXENE@MOF material with Fe3O4@C photon crystal material, prepare the optoelectronic interactive response to the flexible sensor, solve the problem that the existing sensor is difficult to achieve the synchronization detection of light signals and electrical signals, and realizes the high sensitivity and rapid response. Synchronous detection effect.
Patent Information
- Application Number
- CN202411460673.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
AI Technical Summary
Existing sensors need to use different materials and methods when detecting optical and electrical signals, resulting in increased system complexity and increased manufacturing costs, making it difficult to achieve synchronous detection of optical and electrical signals.
The preparation method of photoelectric interactive response flexible sensor is used to combine MXENE@MOF materials with Fe3O4@C photon crystal material to achieve synchronous detection of optical signals and electrical signals. This method includes preparing FE3O4@C magnetic nanoparticles, multi -layer MXENE, and single -layer MXENE@MOF nanoscopic tablets, and combines it with acrylamide monomer, PEGDA, and light -induced agent to form a composite hydrogel flexible sensor.
The synchronous detection of light signals and electrical signals has been realized, with high sensitivity, rapid response and good mechanical properties. It is suitable for real -time monitoring in complex environments, reducing system complexity and cost.
Smart Images

Figure CN119374716A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sensors, and in particular relates to a photoelectric interactive response flexible sensor and a preparation method thereof. Background Art
[0002] Existing sensors usually need to use different materials and methods to detect optical signals and electrical signals respectively. This separate detection method not only increases the complexity of the system, but also significantly increases the manufacturing and operating costs. For example, photosensitive semiconductors and organic photoconductive materials are commonly used for optical signal detection, while electrical signal detection relies on materials such as conductive polymers and metal oxides. These materials each have their own advantages and limitations, but in practical applications, it is often necessary to integrate multiple materials into a system to achieve synchronous detection of optical and electrical signals. This multi-material integration method not only increases the design difficulty of the sensor, but also puts higher requirements on the manufacturing process.
[0003] With the increasing demand for smart devices and health monitoring, it is particularly important to develop an efficient sensor that can detect both optical and electrical signals. Currently, smart wearable devices, medical monitoring instruments, and environmental monitoring systems are in urgent need of a sensor that can detect multiple signals in real time and efficiently to meet complex and changing application requirements. Such sensors not only need to have high sensitivity and fast response capabilities, but also must have good mechanical flexibility and stability to adapt to various application environments. Summary of the invention
[0004] The purpose of the present invention is to provide a photoelectric interactive response flexible sensor and a preparation method thereof, which can realize the synchronous detection and response of light and electrical signals, has high sensitivity, fast response and good mechanical properties, and can be suitable for real-time monitoring of various environmental changes.
[0005] To achieve the above object, the present invention provides a method for preparing a photoelectric interactive response flexible sensor, comprising the following steps:
[0006] Step 1: Add ferrocene to acetone, perform ultrasonic treatment, add a certain amount of hydrogen peroxide, stir well and use solvothermal method to prepare F e3 O4@C magnetic nanoparticles;
[0007] Step 2: Mix a certain amount of hydrochloric acid and lithium fluoride in an oil bath and add a certain amount of Ti3C2T x The powder was magnetically stirred to remove the Al layer, the reaction mixture was centrifuged and washed with deionized water until neutral to obtain multilayer MXene, a certain amount of lithium chloride was mixed with deionized water and multilayer MXene by ion intercalation method, and the multilayer MXene was shaken and peeled off after standing, centrifuged to remove impurities, and freeze-dried to obtain a single layer of Ti3C2Tx MXene nanosheets;
[0008] Step 3: Dissolve copper nitrate trihydrate in methanol, add polyvinyl pyrrolidone to obtain solution A, add MXene powder and trimesic acid to methanol, obtain solution B after ultrasonic dispersion treatment, slowly add solution A to solution B under magnetic stirring, collect the product by centrifugation after complete reaction and wash it three times with methanol, and obtain single-layer MXene@MOF nanosheets after freeze-drying treatment;
[0009] Step 4: Add a certain amount of acrylamide monomer, PEGDA and photoinitiator to ethylene glycol to obtain a mixed solution, and ultrasonically disperse it; add Fe3O4@C magnetic nanoparticles and monolayer MXene@MOF nanosheets to the mixed solution in proportion, and ultrasonically disperse it; infiltrate the mixed solution between glass sheets and place it on a rectangular rubidium magnet to form a photonic crystal array with bright structural colors; after cross-linking under ultraviolet light, repeatedly wash with deionized water to obtain a composite hydrogel flexible sensor; a series of structural color flexible sensors can be prepared by regulating the particle size of Fe3O4@C magnetic nanoparticles.
[0010] As a further scheme of the present invention: in step 1, a 100 ml brown conical flask is used as a container for stirring and mixing ferrocene and acetone, the amount of ferrocene used is 0.54 g, the amount of acetone used is 54 ml, and the ultrasonic treatment time is 30 min; after the solution is ultrasonicated, 1.0 ml-1.4 ml of 30% hydrogen peroxide is added, and the mixture is magnetically stirred at a speed of 500 rpm for 2 h to obtain a mixed solution.
[0011] As a further solution of the present invention: the solvothermal method is to add the mixed liquid to a para-polyphenol lining with a volume of 100 ml, seal it with a stainless steel reactor, place it in an oven, the reaction temperature is 220°C, and the reaction time is 72 hours; then the product is taken out and separated with a neodymium magnet, and after removing the solvent and impurities, it is washed multiple times with anhydrous ethanol. The final product is dried in an oven at 60°C for 1 hour to obtain Fe3O4@C magnetic nanoparticles.
[0012] As a further scheme of the present invention: in step 2, polytetrafluoroethylene is used as a container for mixing hydrochloric acid and lithium fluoride in an oil bath, the amount of hydrochloric acid is 20 mL, the amount of lithium fluoride is 1 g-1.4 g, the temperature of the oil bath stirring of the two is 42 ° C, and the stirring time is 10 min; then 1 g-1.4 g of Ti3AlC2 powder is added, and magnetic stirring is carried out at 42 ° C for 24 hours to remove the Al layer, and the speed is 500 rpm; after the reaction, the mixture is centrifuged at 3000 rpm for 5 minutes, and the precipitate is collected and washed with deionized water; the centrifugation and washing are repeated until pH = 7 to obtain multilayer MXene; when the multilayer MXene is stripped by the ion intercalation method, 1.2 g-1.6 g of lithium chloride is mixed with 20 mL of deionized water and multilayer MXene, and the multilayer MXene is stripped after standing for 5 minutes; the impurities are removed by centrifugation at 6000 rpm, and then centrifuged at 9000 rpm for 10 minutes, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets.
[0013] As a further scheme of the present invention: in step 3, 0.9 g of copper nitrate trihydrate is dissolved in 50 mL of methanol, and 0.4 g of polyvinyl pyrrolidone is added to obtain solution A; 20 mg of MXene powder and 0.43 g of trimesic acid are added to 50 mL of methanol, and the ultrasonic treatment time is 30 min to obtain solution B; under 500 rpm magnetic stirring, solution A is slowly added dropwise to solution B, and the reaction time is 2 h; the product is centrifuged at a speed of 8000 rpm and a centrifugation time of 7 min. The product is collected and washed three times with methanol, and a single-layer MXene@MOF nanosheet is obtained after freeze-drying.
[0014] As a further scheme of the present invention: in step 4, 1g acrylamide monomer, 0.1g PEGDA, 0.1g photoinitiator 2959 and 8.8g ethylene glycol are prepared to obtain a mixed solution, and the ultrasonic treatment time is 30min; 140mg-160mg of Fe3O4@C nanoparticles and 12mg of single-layer MXene@MOF nanosheets are added to the mixed solution, and the ultrasonic treatment time is 2h; the uniformly dispersed mixed solution is infiltrated between glass sheets with a spacing of 0.5mm between the glass sheets, and placed on a 50mm×50mm×20mm rectangular rubidium magnet to form a photonic crystal array with different structural colors; cross-linked under ultraviolet light with a wavelength of 365nm for 1h; repeatedly washed with deionized water to obtain a hydrogel flexible sensor.
[0015] To achieve the above objectives, the present invention also provides a photoelectric interactive response flexible sensor, which is prepared by any one of the above preparation methods.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] MXene is a new type of two-dimensional transition metal carbide or nitride, with metal-like conductivity, high specific surface area and excellent mechanical flexibility; MOF materials are known for their high specific surface area, adjustable pore structure and rich surface chemical properties; by combining MXene@MOF materials with Fe3O4@C photonic crystal materials, the coordinated optimization of material properties can be achieved, and the simultaneous detection of optical and electrical signals can be realized, with the characteristics of high sensitivity and rapid response. At the same time, the sensor shows excellent stability and durability in complex environments, and is suitable for a variety of application scenarios such as flexible sensing and smart wearable devices, effectively reducing the complexity and cost of the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 a is the SEM image of Fe3O4@C nanoparticles; b and c are TEM images of Fe3O4@C nanoparticles; Figure 1 d is the distribution diagram of C, Fe and O elements in Fe3O4@C nanoparticles.
[0019] Figure 2 a is the SEM image of a MXene@MOF single-layer nanosheet; b and c are the Ti and Cu element distribution maps of the nanosheet; d is a side view of a MXene@MOF single-layer nanosheet; e is the porous structure of the hydrogel flexible sensor; f and g are the C element distribution maps of the hydrogel and the SEM images of the MXene@MOF nanosheet in the hydrogel network; h and i are the Ti and Cu element distribution maps of the nanosheet; j is a schematic diagram of the flexible sensor; k and I are chain structure diagrams composed of Fe3O4@C nanoparticles in the hydrogel.
[0020] Figure 3 Photos and reflection spectra of flexible sensors with different structural colors prepared using Fe3O4@C nanoparticles with different particle sizes.
[0021] Figure 4 (a) is a photograph of the flexible sensor's optical response to finger joint bending; (b) is a response cycle diagram of the optical and electrical signals during the finger bending-recovery process.
[0022] Figure 5 This is the optoelectronic interactive response diagram of the flexible sensor to local pressure. DETAILED DESCRIPTION
[0023] The present invention will be further described below by way of examples.
[0024] A method for preparing a photoelectric interactive response flexible sensor comprises the following steps:
[0025] Step 1: Add ferrocene to acetone, perform ultrasonic treatment, add a certain amount of hydrogen peroxide, stir well and use solvothermal method to prepare F e3 O4@C magnetic nanoparticles;
[0026] Step 2: Mix a certain amount of hydrochloric acid and lithium fluoride in an oil bath and add a certain amount of Ti3C2T x The powder was magnetically stirred to remove the Al layer, the reaction mixture was centrifuged and washed with deionized water until neutral to obtain multilayer MXene, a certain amount of lithium chloride was mixed with deionized water and multilayer MXene by ion intercalation method, and the multilayer MXene was shaken and peeled off after standing, centrifuged to remove impurities, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets;
[0027] Step 3: Dissolve copper nitrate trihydrate in methanol, add polyvinyl pyrrolidone to obtain solution A, add MXene powder and trimesic acid to methanol, obtain solution B after ultrasonic dispersion treatment, slowly add solution A to solution B under magnetic stirring, collect the product by centrifugation after complete reaction and wash it three times with methanol, and obtain single-layer MXene@MOF nanosheets after freeze-drying treatment;
[0028] Step 4: Add a certain amount of acrylamide monomer, PEGDA and photoinitiator to ethylene glycol to obtain a mixed solution, and ultrasonically disperse it; add Fe3O4@C magnetic nanoparticles and monolayer MXene@MOF nanosheets to the mixed solution in proportion, and ultrasonically disperse it; infiltrate the mixed solution between glass sheets and place it on a rectangular rubidium magnet to form a photonic crystal array with bright structural colors; after cross-linking under ultraviolet light, repeatedly wash with deionized water to obtain a composite hydrogel flexible sensor; a series of structural color flexible sensors can be prepared by regulating the particle size of Fe3O4@C magnetic nanoparticles.
[0029] The following combination Figures 1 to 5 The effect diagram and specific embodiments are described.
[0030] Embodiment 1:
[0031] 0.54g ferrocene and 54ml acetone were added to a brown conical flask with a capacity of 100ml, and ultrasonic treatment was carried out for 30min; after complete dissolution, 1.0ml 30% hydrogen peroxide was added, and magnetic stirring was carried out at a speed of 500rpm for 2h to obtain a mixed solution; the mixed solution was added to a para-polyphenol liner with a volume of 100ml, sealed with a stainless steel reactor, and placed in an oven, the reaction temperature was 220℃, and the reaction time was 72h; then the product was taken out and separated with a neodymium magnet, and after removing the solvent and impurities, it was washed several times with anhydrous ethanol, and the final product was dried in an oven at 60℃ for 1h to obtain Fe3O4@C magnetic nanoparticles with an average particle size of 143nm and a reflection wavelength of 495nm.
[0032] In a polytetrafluoroethylene container, add 20mL hydrochloric acid and 1g lithium fluoride, stir in a 42℃ oil bath for 10min, then slowly add 1g Ti3AlC2 powder, magnetically stir at 42℃ for 24h to remove the Al layer; centrifuge the reaction mixture at 3000rpm for 5min, collect the precipitate and wash with deionized water; repeat centrifugation until pH=7 to obtain multilayer MXene. Through the ion intercalation method, 1.2g lithium chloride is mixed with 20mL deionized water and multilayer MXene, and the multilayer MXene is shaken and peeled off after standing for 5min; centrifuge at 6000rpm to remove impurities, and then centrifuge at 9000rpm for 10min, and freeze-dry to obtain a single layer of Ti3C2T x MXene nanosheets.
[0033] 0.9 g of copper nitrate trihydrate was dissolved in 50 mL of methanol, and 0.4 g of polyvinyl pyrrolidone was added to obtain solution A. 20 mg of MXene powder and 0.43 g of trimesic acid were added to 50 mL of methanol, and the ultrasonic treatment time was 30 min to obtain solution B. Under magnetic stirring at 500 rpm, solution A was slowly added dropwise to solution B, and the reaction time was 2 h. The product was centrifuged at a speed of 8000 rpm and a centrifugal time of 7 min. The product was collected and washed three times with methanol, and then freeze-dried to obtain a single-layer MXene@MOF nanosheet.
[0034] Prepare a mixed solution of 1g acrylamide monomer, 0.1g PEGDA, 0.1g photoinitiator 2959 and 8.8g ethylene glycol, and ultrasonically treat for 30min; add 140mg Fe3O4@C nanoparticles and 12mg monolayer MXene@MOF nanosheets to the mixed solution, and ultrasonically treat for 2h; infiltrate the uniformly dispersed solution between glass sheets with a spacing of 0.5mm between the glass sheets, place on a 50mm×50mm×20mm rectangular nephrite magnet, and crosslink for 1h under ultraviolet light with a wavelength of 365nm. Repeatedly wash with deionized water to obtain a hydrogel flexible sensor with blue structural color.
[0035] Embodiment 2:
[0036] 0.54g of ferrocene and 54ml of acetone are added to a brown conical flask with a capacity of 100ml, and ultrasonic treatment is carried out for 30min; after complete dissolution, 1.2ml of 30% hydrogen peroxide is added, and magnetic stirring is carried out at a speed of 500rpm for 2h to obtain a mixed solution; the mixed solution is added to a para-polyphenol liner with a volume of 100ml, sealed with a stainless steel reactor, and placed in an oven, the reaction temperature is 220℃, and the reaction time is 72h; then the product is taken out and separated with a neodymium magnet, and after removing the solvent and impurities, it is washed several times with anhydrous ethanol, and the final product is dried in an oven at 60℃ for 1h to obtain Fe3O4@C magnetic nanoparticles with an average particle size of 185nm and a reflection wavelength of 565nm.
[0037] In a polytetrafluoroethylene container, 20 mL of hydrochloric acid and 1.2 g of lithium fluoride were added and stirred in an oil bath at 42 °C for 10 min. Then, 1.2 g of Ti3AlC2 powder was slowly added and magnetically stirred at 42 °C for 24 h to remove the Al layer. The reaction mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected and washed with deionized water. Centrifugation was repeated until pH = 7 to obtain multilayer MXene. By ion intercalation, 1.4 g of lithium chloride was mixed with 20 mL of deionized water and multilayer MXene, and the multilayer MXene was shaken and peeled off after standing for 5 min. Impurities were removed by centrifugation at 6000 rpm, and then centrifuged at 9000 rpm for 10 min, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets.
[0038] 0.9 g of copper nitrate trihydrate was dissolved in 50 mL of methanol, and 0.4 g of polyvinyl pyrrolidone was added to obtain solution A. 20 mg of MXene powder and 0.43 g of trimesic acid were added to 50 mL of methanol, and the ultrasonic treatment time was 30 min to obtain solution B. Under magnetic stirring at 500 rpm, solution A was slowly added dropwise to solution B, and the reaction time was 2 h. The product was centrifuged at a speed of 8000 rpm and a centrifugal time of 7 min. The product was collected and washed three times with methanol, and then freeze-dried to obtain a single-layer MXene@MOF nanosheet.
[0039] A mixed solution of 1g acrylamide monomer, 0.1g PEGDA, 0.1g photoinitiator 2959 and 8.8g ethylene glycol was prepared, and the ultrasonic treatment time was 30min; 150mg Fe3O4@C nanoparticles and 12mg single-layer MXene@MOF nanosheets were added to the mixed solution, and the ultrasonic treatment time was 2h; the evenly dispersed solution was infiltrated between glass sheets with a spacing of 0.5mm between the glass sheets, placed on a 50mm×50mm×20mm rectangular nephelodonium magnet, and cross-linked under ultraviolet light with a wavelength of 365nm for 1h; repeatedly washed with deionized water to obtain a hydrogel flexible sensor with a green structural color.
[0040] Embodiment 3:
[0041] 0.54g of ferrocene and 54ml of acetone are added to a brown conical flask with a capacity of 100ml, and ultrasonic treatment is carried out for 30min; after complete dissolution, 1.4ml of 30% hydrogen peroxide is added, and magnetic stirring is carried out at a speed of 500rpm for 2h to obtain a mixed solution; the mixed solution is added to a para-polyphenol liner with a volume of 100ml, sealed with a stainless steel reactor, and placed in an oven, the reaction temperature is 220℃, and the reaction time is 72h; then the product is taken out and separated with a neodymium magnet, and after removing the solvent and impurities, it is washed several times with anhydrous ethanol, and the final product is dried in an oven at 60℃ for 1h to obtain Fe3O4@C magnetic nanoparticles with an average particle size of 223nm and a reflection wavelength of 645nm.
[0042] In a polytetrafluoroethylene container, 20 mL of hydrochloric acid and 1.4 g of lithium fluoride were added and stirred in an oil bath at 42 °C for 10 min. Then, 1.4 g of Ti3AlC2 powder was slowly added and magnetically stirred at 42 °C for 24 h to remove the Al layer. The reaction mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected and washed with deionized water. Centrifugation was repeated until pH = 7 to obtain multilayer MXene. By ion intercalation, 1.6 g of lithium chloride was mixed with 20 mL of deionized water and multilayer MXene, and the multilayer MXene was shaken and peeled off after standing for 5 min. Impurities were removed by centrifugation at 6000 rpm, and then centrifuged at 9000 rpm for 10 min, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets.
[0043] 0.9 g of copper nitrate trihydrate was dissolved in 50 mL of methanol, and 0.4 g of polyvinyl pyrrolidone was added to obtain solution A. 20 mg of MXene powder and 0.43 g of trimesic acid were added to 50 mL of methanol, and the ultrasonic treatment time was 30 min to obtain solution B. Under magnetic stirring at 500 rpm, solution A was slowly added dropwise to solution B, and the reaction time was 2 h. The product was centrifuged at a speed of 8000 rpm and a centrifugal time of 7 min. The product was collected and washed three times with methanol, and then freeze-dried to obtain a single-layer MXene@MOF nanosheet.
[0044] A mixed solution of 1g acrylamide monomer, 0.1g PEGDA, 0.1g photoinitiator 2959 and 8.8g ethylene glycol was prepared, and the ultrasonic treatment time was 30min; 160mg Fe3O4@C nanoparticles and 12mg single-layer MXene@MOF nanosheets were added to the mixed solution, and the ultrasonic treatment time was 2h; the evenly dispersed mixed solution was infiltrated between glass sheets with a spacing of 0.5mm between the glass sheets, placed on a 50mm×50mm×20mm rectangular nephelodonium magnet, and cross-linked under ultraviolet light with a wavelength of 365nm for 1.5h; repeatedly washed with deionized water to obtain a hydrogel flexible sensor with a red structural color.
Claims
1. A method for preparing a photoelectric interactive response flexible sensor, characterized in that: The following steps are involved: Step 1: Add ferrocene to acetone, perform ultrasonic treatment, add a certain amount of hydrogen peroxide, stir well and use solvothermal method to prepare F e3 O4@C magnetic nanoparticles; Step 2: Mix a certain amount of hydrochloric acid and lithium fluoride in an oil bath and add a certain amount of Ti3C2T x The powder was magnetically stirred to remove the Al layer, the reaction mixture was centrifuged and washed with deionized water until neutral to obtain multilayer MXene, a certain amount of lithium chloride was mixed with deionized water and multilayer MXene by ion intercalation method, and the multilayer MXene was shaken and peeled off after standing, centrifuged to remove impurities, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets; Step 3: Dissolve copper nitrate trihydrate in methanol, add polyvinyl pyrrolidone to obtain solution A, add MXene powder and trimesic acid to methanol, obtain solution B after ultrasonic dispersion treatment, slowly add solution A to solution B under magnetic stirring, collect the product by centrifugation after complete reaction and wash it three times with methanol, and obtain single-layer MXene@MOF nanosheets after freeze-drying treatment; Step 4: Add a certain amount of acrylamide monomer, PEGDA and photoinitiator to ethylene glycol to obtain a mixed solution, and ultrasonically disperse it; add Fe3O4@C magnetic nanoparticles and monolayer MXene@MOF nanosheets to the mixed solution in proportion, and ultrasonically disperse it; infiltrate the mixed solution between glass sheets and place it on a rectangular rubidium magnet to form a photonic crystal array with bright structural colors; after cross-linking under ultraviolet light, repeatedly wash with deionized water to obtain a composite hydrogel flexible sensor; a series of structural color flexible sensors can be prepared by regulating the particle size of Fe3O4@C magnetic nanoparticles.
2. The method for preparing a photoelectric interactive response flexible sensor according to claim 1, characterized in that: In step 1, a 100 ml brown conical flask is used as a container for stirring and mixing ferrocene and acetone, the amount of ferrocene used is 0.54 g, the amount of acetone used is 54 ml, and the ultrasonic treatment time is 30 min; after the solution is ultrasonicated, 1.0 ml to 1.4 ml of 30% hydrogen peroxide is added, and the mixture is magnetically stirred at a speed of 500 rpm for 2 h to obtain a mixed solution.
3. The method for preparing a photoelectric interactive response flexible sensor according to claim 2, characterized in that: The solvothermal method is to add the mixed liquid to a 100ml volume of para-polyphenol lining, seal it with a stainless steel reactor, and place it in an oven. The reaction temperature is 220°C and the reaction time is 72h. The product is then taken out and separated with a neodymium magnet. After removing the solvent and impurities, it is washed multiple times with anhydrous ethanol. The final product is dried in an oven at 60°C for 1h to obtain Fe3O4@C magnetic nanoparticles.
4. The method for preparing a photoelectric interactive response flexible sensor according to claim 1, characterized in that: In step 2, polytetrafluoroethylene is used as a container for mixing hydrochloric acid and lithium fluoride in an oil bath, the amount of hydrochloric acid is 20 mL, the amount of lithium fluoride is 1 g-1.4 g, the temperature of the oil bath stirring of the two is 42 ° C, and the stirring time is 10 min; then 1 g-1.4 g of Ti3AlC2 powder is added, and magnetic stirring is carried out at 42 ° C for 24 h to remove the Al layer, and the speed is 500 rpm; after the reaction, the mixture is centrifuged at 3000 rpm for 5 min, and the precipitate is collected and washed with deionized water; the centrifugation and washing are repeated until pH = 7 to obtain multilayer MXene; when the multilayer MXene is stripped by the ion intercalation method, 1.2 g-1.6 g of lithium chloride is mixed with 20 mL of deionized water and multilayer MXene, and the multilayer MXene is stripped after standing for 5 min; the impurities are removed by centrifugation at 6000 rpm, and then centrifuged at 9000 rpm for 10 minutes, and freeze-dried to obtain a single layer of Ti3C2T x MXene nanosheets.
5. The method for preparing a photoelectric interactive response flexible sensor according to claim 1, characterized in that: In step 3, 0.9 g of copper nitrate trihydrate was dissolved in 50 mL of methanol, and 0.4 g of polyvinyl pyrrolidone was added to obtain solution A; 20 mg of MXene powder and 0.43 g of trimesic acid were added to 50 mL of methanol, and the ultrasonic treatment time was 30 min to obtain solution B; under 500 rpm magnetic stirring, solution A was slowly added dropwise to solution B, and the reaction time was 2 h; the product was centrifuged at a speed of 8000 rpm and a centrifugation time of 7 min. The product was collected and washed three times with methanol, and a single-layer MXene@MOF nanosheet was obtained after freeze-drying.
6. The method for preparing a photoelectric interactive response flexible sensor according to claim 1, characterized in that: In step 4, 1 g acrylamide monomer, 0.1 g PEGDA, 0.1 g photoinitiator 2959 and 8.8 g ethylene glycol are prepared to obtain a mixed solution, and the ultrasonic treatment time is 30 min; 140 mg-160 mg of Fe3O4@C nanoparticles and 12 mg of single-layer MXene@MOF nanosheets are added to the mixed solution, and the ultrasonic treatment time is 2 h; the uniformly dispersed mixed solution is infiltrated between glass sheets with a spacing of 0.5 mm between the glass sheets, and placed on a 50 mm × 50 mm × 20 mm rectangular nedium magnet to form a photonic crystal array with different structural colors; cross-linked under ultraviolet light with a wavelength of 365 nm for 1 h; repeatedly washed with deionized water to obtain a hydrogel flexible sensor.
7. A photoelectric interactive response flexible sensor, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.